Activation of AMPK/Nrf2 signalling by Manuka honey protects human dermal fibroblasts against oxidative damage by improving antioxidant response and mitochondrial function promoting wound healing. (August 2016) - Alvarez-Suarez, José Miguel; Giampieri, Francesca; Cordero, Mario; Gasparrini, Massimiliano; Forbes-Hernández, Tamara Yuliet; Mazzoni, Luca; Afrin, Sadia; Beltrán-Ayala, Pablo; González-Paramás, Ana María; Santos-Buelga, Celestino; Varela-Lopez, Alfonso; Quiles, José Luis; et al.
Highlights: Manuka honey protects against oxidative stress, improving mitochondrial functionality. Manuka honey activates AMPK/Nrf2/ARE pathway, enhancing antioxidant defence. Manuka honey promotes the healing of wounds. Abstract: Excessive amounts of free radicals are deleterious for cells, resulting in cell damage, affecting the wound healing process and causing premature ageing or even neoplastic transformation. Here the capacity of Manuka honey (MH) to protect against oxidative damage and improve the process of skin wound healing was investigated. Up to 16 compounds were identified in MH, with leptosin derivatives and methyl syringate as the major ones. MH protected against apoptosis, intracellular ROS production, and lipid and protein oxidative damage. MH also protected mitochondrial functionality, promoted cell proliferation and activated the AMPK/Nrf2/ARE signalling pathway, as well as the expression of the antioxidant enzymes such as SOD and CAT. Here we describe for the first time that one of the possible mechanisms by which MH exhibits its ability to promote wound healing could be due to its capacity to improve the antioxidant response by activating AMPK phosphorylation and the ARE response.